Genome sequencing of pediatric medulloblastoma links catastrophic DNA rearrangements with TP53 mutations - Rausch, Tobias; Remke, Marc; Wang, Qi; Witt, Hendrik; Bender, Sebastian; Pleier, Sabrina Valesca; Beck, Christian; Deimling, Andreas von; Eils, Roland; Kulozik, Andreas; Witt, Olaf; Korshunov, Andrey; et al. (Cell, 2012)
Summary Genomic rearrangements are thought to occur progressively during tumor development. Recent findings, however, suggest an alternative mechanism, involving massive chromosome rearrangements in a one-step catastrophic event termed chromothripsis. We report the whole-genome sequencing-based analysis of a Sonic-Hedgehog medulloblastoma (SHH-MB) brain tumor from a patient with a germline TP53 mutation (Li-Fraumeni syndrome), uncovering massive, complex chromosome rearrangements. Integrating TP53 status with microarray and deep sequencing-based DNA rearrangement data in additional patients reveals a striking association between TP53 mutation and chromothripsis in SHH-MBs. Analysis of additional tumor entities substantiates a link between TP53 mutation and chromothripsis, and indicates a context-specific role for p53 in catastrophic DNA rearrangements. Among these, we observed a strong association between somatic TP53 mutations and chromothripsis in acute myeloid leukemia. These findings connect p53 status and chromothripsis in specific tumor types, providing a genetic basis for understanding particularly aggressive subtypes of cancer.
Gesehen am 17.04.2018